ANALISIS PERBEDAAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SEBELUM DAN SETELAH PENGUMUMAN KABINET INDONESIA BERSATU TAHAP II PADA PERUSAHAAN LQ-45 - Marlinda Saputri; Setiawati Setiawati (Jurnal Ilmiah Hospitality, 2023)
This study aims to see the reaction of the capital market to an event or political event on a national scale. In this study, the stocks used as samples were stocks from LQ-45 companies listed on the Indonesia Stock Exchange totaling 45 companies. Research using an event study approach regarding the relationship between differences in abnormal returns and trading volume on the announcement of the united Indonesia cabinet phase II tested two hypotheses regarding the reaction of LQ-45 companies on the Indonesia Stock Exchange. The results of the study show that Cabinet announcements contain information that cannot increase abnormal returns and do not contain information that can significantly increase trading volume.